Brand Love Among Female Consumers for Fashion Clothing - Rajput, Amer; Batool, Saba; Ahmad Khan, Faheem (UUM Press, 2020)
The purpose of this study is to investigate the association of brand anthropomorphism with anticipated separation distress through mediation of brand love among female consumers for fashion clothing brands. The conceptual research framework was empirically tested and data were collected through the questionnaire survey of 302 female consumers of fashion clothing brands in Pakistan. The structural equation modelling with partial least squares (SEM-PLS) is used to analyse the conceptual research framework. An explicit description is presented about the positive association of brand anthropomorphism with the anticipated separation distress through the mediation of brand love for fashion clothing among female. This study has empirically proven the positive association of brand anthropomorphism with the anticipated separation distress of brand love among female consumers for fashion clothing. Additionally, this study enhances the knowledge of brand love in the context of female consumers and managers of clothing brands.